Perlindungan Hukum Pelaku Usaha Atas Penggunaan Economic Evidence Sebagai Alat Bukti Petunjuk Dalam Hukum Persaingan Usaha di Indonesia - Melkisedek Vajar Silaban; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Differences in perspective on the position of economic evidence as evidence in business competition law in Indonesia at the level of the Business Competition Supervisory Commission, District Court, to the Supreme Court occur or are caused by no conformity of regulations related to the use of evidence in Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Business Competition resulting in frequent KPPU decisions being canceled. The study entitled